TI_GERICHTE 52.2021.45 vom 23. Dezember 2020 , Diniego di licenza per la formazione di opere fuori della zona edificabile - TI Tribunale d'appello (2020)
Diniego di licenza per la formazione di opere fuori della zona edificabile